PENGUATAN BUDAYA LITERASI DESA MELALUI PROGRAM KKN PMD: STUDI KASUS DESA TERONG TAWAH - Azizy, Muhamad; Jurnal Wicara; Wulandari, Heryca; Indriani, Yulia; Maulidna, Maizati; Putri, Athifah; Islam, Egista; Yuniardi, Lalu; Yuhendra, Kayla; Sriwahyuni, Yuyun; Zulpazlyawan, M.; Dewi, Suprayanti; Azizy, Muhammad (Jurnal Wicara, 2025)
The Community Service Program (KKN PMD) of Universitas Mataram was carried out in Terong Tawah Village, Labuapi District, West Lombok Regency, with the aim of strengthening the village’s literacy culture through the revitalization of the As-Suhada Community Reading Park (TBM). The background of this program lies in the low literacy level of the community, the suboptimal management of TBM, and the limited participation of residents in reading activities. This study employed a descriptive qualitative method with a participatory approach through observation, interviews, documentation, and students’ reflective notes. The results show significant changes in TBM management through the cataloguing and reorganization of 1,000 book collections and the issuance of membership cards. Interactive literacy programs also proved effective. In the Cerdas Mengulas Buku activity, involving 21 fourth-grade students at SDN 3 Terong Tawah, 20 students successfully answered comprehension questions, while one required further assistance. In the Writing Stories Based on Reading program, attended by 25 sixth-grade students, writing scores improved from 60–70 in the pre-test to 75–90 in the post-test after remedial guidance. Furthermore, the Read Me a Book and Reading Aloud activities engaged 30 kindergarten students of As-Suhada and 30 preschool students, fostering reading interest and confidence. Overall, interactive literacy programs such as Cerdas Mengulas Buku and Writing Stories Based on Reading proved to be effective models in enhancing children’s reading interest, comprehension skills, and writing creativity. For sustainability, village institutional support, the diversification of reading collections, and the empowerment of local literacy cadres are needed so that Terong Tawah can develop into an inclusive and sustainable literacy village.